Kajian Yuridis Tindak Pidana Pemalsuan Surat Secara Bersama-Sama (Studi Kasus Putusan Pengadilan Negeri Jakarta Timur Nomor 305/Pid.B/2021/PN Jkt.Timur ) - I Gede Eka Suantara; I Nyoman Gede Sugiartha; Ni Made Sukaryati Karma (Warmadewa Press, 2022)
Indonesia is a legal state in which all aspects are regulated by applicable law to determine the obligations, rights and obligations in monitoring one's own and social desires. One of the problems in the application of the law that often occurs in events in the community environment is the crime of criminal cases, namely forgery of letters so that there is a criminal act of counterfeiting letters which is formed to provide legal protection. together or participation. The purposes of this study are to analyze the form of criminal sanctions jointly in committing the crime of forgery of letters and the legal considerations given by the panel of judges in imposing punishment on the perpetrators of the crime of forging letters which are carried out together. This research method uses a normative legal method with a statutory approach and a conceptual approach. The data collection technique was carried out using library techniques. The sources of law used are primary and secondary sources of law. The data analysis technique was carried out qualitatively. The findings show that the joint form of criminal sanctions in carrying out the criminal act of forging letters together can be imposed as described in Article 263 paragraph (1) of the Criminal Code regarding the crime of forging letters, threatened with imprisonment for a maximum of six years. Then in Article 55 paragraph (1) 1 of the Criminal Code regarding participation.